Guideline-recommended basic parameter adherence in neurocritical care stroke patients: observational multicenter individual participant data analysis - Mrochen, Anne; Alhaj Omar, Omar; Pelz, Johann O; Michalski, Dominik; Neugebauer, Hermann; Lehrieder, Dominik; Knier, Benjamin; Ringmaier, Corinna; Stetefeld, Henning; Schönenberger, Silvia; Chen, Min; Schneider, Hauke; et al. (European stroke journal, 2025)
Introduction: Neurocritical care patients with neurovascular disease often face poor long-term outcomes, highlighting the pivotal role of evidence-based interventions. Although International Guidelines emphasize managing basic physiological parameters like temperature, blood glucose, blood pressure, and oxygen levels, physician adherence to these targets remains uncertain. This study aimed to assess adherence to guideline-based treatment targets for basic physiological parameters in neurocritical care. - Patients and Methods: This multicenter observational study was conducted across eight tertiary University Hospitals in Germany analyzed 474 patients requiring mechanical ventilation (between January 1st and December 31st, 2021). Adherence was defined as the rate of measurements within therapeutic ranges for systolic blood pressure (situation-adapted), mean blood pressure (MAP, 60-90 mmHg), glucose levels (80-180 mg/dl), body temperature (<37.5°C), partial arterial pressure of oxygen (PaO2) 80-120 mmHg und partial arterial pressure of carbon dioxide (PaCO2) 35-45 mmHg during the initial 96 h of hospitalization in 4 hour-intervals. - Results: Overall, 70.7% of all measurements were within the predetermined therapeutic ranges including SBP (71.3%), temperature (68.3%), MAP (71.4%), PaO2 (65.2%), PaCO2 (75.0%) and blood glucose (80.7%). - Discussion and Conclusion: This multicenter study demonstrates adherence to guideline-based treatment targets, underscoring the high standards maintained by neurological intensive care units. Our study offers valuable insights into adherence to guideline-based treatment targets for neurocritical care patients in Germany. To improve patient care and optimize therapeutic strategies in neurovascular diseases, further research is needed to examine the impact of these adherence parameters on long-term outcomes.